2006
DOI: 10.1086/507703
|View full text |Cite
|
Sign up to set email alerts
|

Principle of Universality of γ-Process Nucleosynthesis in Core-Collapse Supernova Explosions

Abstract: Using core-collapse supernova explosion models, we investigate the principle of the universality of the gprocess, according to which the s/p abundance ratios produced by individual nucleosynthesis episode are almost constant over a wide range of atomic number. The universality originates from the shift of the g-process layers, the independence of the s/p abundance ratios of the nuclear reactions, and the weak s-process in presupernovae. Our calculations further suggest an extended universality in which the s/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…We calculated the γ process of core-collapse supernovae under various astrophysical conditions such as, metallicity, progenitor mass, and explosion energy and found that the scalings hold for individual nucleosyntheses independent of the astrophysical conditions assumed [27]. We presented a detailed mechanism why the scalings fold for various supernovae in our previous papers [27,28]. Our proposed chronometer is based on the universality of the scaling for the two p-nuclei.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…We calculated the γ process of core-collapse supernovae under various astrophysical conditions such as, metallicity, progenitor mass, and explosion energy and found that the scalings hold for individual nucleosyntheses independent of the astrophysical conditions assumed [27]. We presented a detailed mechanism why the scalings fold for various supernovae in our previous papers [27,28]. Our proposed chronometer is based on the universality of the scaling for the two p-nuclei.…”
mentioning
confidence: 95%
“…In addition, we found a novel concept of "the universality of the γ process", wherein the scalings hold for nuclides produced in individual supernova γ processes under various astrophysical conditions [26]. We calculated the γ process of core-collapse supernovae under various astrophysical conditions such as, metallicity, progenitor mass, and explosion energy and found that the scalings hold for individual nucleosyntheses independent of the astrophysical conditions assumed [27]. We presented a detailed mechanism why the scalings fold for various supernovae in our previous papers [27,28].…”
mentioning
confidence: 99%
“…We found the empirical scaling law that the abundance ratios of N(1st p)/N(2nd p) is almost constant in a wide region of atomic number, where N is the solar abundance [4]. This empirical law leads to "the universality of the γ-process" that the scaling holds for nuclei produced in individual SNe [4,15]. If the abundances of 136,138 Ce and 138 La in a single sample produced mainly by a single supernova are measured, the time elapsed from a ν-process episode, T , can be calculated by 1) where N is the observed abundance in the sample, R pp is the initial N(1st p)/N(2nd p) ratio at the freezeout of the γ-process, and b is the branching ratio of the β − decay of 138 La: λ (β − ) / (λ (β − )+λ (EC)).…”
Section: Pos(nic-ix)112mentioning
confidence: 99%
“…In our previous paper [14], we reported two empirical scaling laws in the solar system abundances, which are a piece of evidence that the most probable origin of the 27 p-nuclei is γ-process in SNe. These scalings lead to a novel concept of "the universality of the γ-process" [14,15]. The understanding of the mechanism of the universality is crucial for the γ-process and the Galactic chemical evolution (GCE) of the p-and s-nuclei.…”
Section: Introductionmentioning
confidence: 99%